Predictors of mood response to acute tryptophan depletion. A reanalysis. - Booij, L; Van der Does, W; Benkelfat, C; Bremner, J; Cowen, P; Fava, M; Gillin, C; Leyton, M; Moore, P; Smith, K; Van der Kloot, W (2002)
Acute tryptophan depletion (ATD) induces depressive symptoms in 50-60% of selective serotonin reuptake inhibitor (SSRI) treated, recovered depressed patients. However, no reliable predictors of mood response to ATD have been established. In the present study, individual subject data of six ATD studies were pooled ('mega-analysis') in order to investigate the mediating role of clinical, demographic and biochemical characteristics in the mood response to ATD. A procedure was developed to make different versions of the Hamilton scale comparable. Recurrent depressive episodes, female gender, prior exposure to SSRI antidepressant treatment and previous serious suicidal thoughts/attempts all appear to be independent predictors of mood response to ATD. Chronicity of illness is the most powerful predictor. Residual symptoms of depression were not found to predict response to ATD. ATD may be useful to study the mechanism of action of SSRI antidepressants and individual biological vulnerability of the serotonin system. Whether the effects of ATD represent a reversal of the action of SSRI antidepressants or individual vulnerability probably depends upon the timing of the procedure in the course of remission of a depressive episode.